(untitled) (Research, Society and Development, 2022)
A 2017 survey entitled Media Property Monitor (MOM) and organized by Reporters Without Borders shows that Brazil has the worst indicators for media plurality among 12 developing countries. Four of the main Brazilian TV networks account for more than 71% of the entire audience in the country. Contrary to these media conglomerates there is the concept of free media characterized as an alternative media to the oligarchic communication models that make up the Brazilian media scenario. Given this context, this article aims to analyze the discourses that the Brazilian collective Intervozes makes about itself by calling itself a free and democratic media. The corpus of this study comprises four texts from the official Intervozes website: Who we are, Charter of Principles, Areas of Action Human Rights and Public and Popular Communication. Anchored on the theoretical methodological assumption of Discourse Analysis (DA) which understands that every discourse is a social construction with the aim of generating meanings, this study uses the theorists Benetti (2008), Ferreira (2010), Foucault (1995), Orlandi (1999), Paulillo (2002), Pinto (1999), among others, to address the conditions of production and discursive formation. We also approach communication and democracy from the perspective of Chauí (2018), Kucinsky (2003), Vilela (2018) and others. The results point to a self-assertive discourse in the sense that Intervozes understands itself as a transforming agent as a new means of communication and wishes to reinforce this sense in the reader.